Dukungan Suami, Pengetahuan Ibu Hamil Trimester III dengan Pelaksanaan Program Perencanaan Persalinan dan Pencegahan Komplikasi (P4K) di Puskesmas Kassi-Kassi Kota Makassar - Ulfah Ilyas; Maria Sonda; Hidayati Hidayati (Media Kesehatan Politeknik Kesehatan Makassar, 2020)
Results of a preliminary study conducted by the author on 28 November 2018 in Kassi-Kassi Health Center Public City of Makassar were interviews with 11 third trimester pregnant women who visited antenatal check, 8 (70%) of pregnant women have not planned where labor, labor companion, potential blood donors and the sticker affixed on the door P4K yet home mom for not knowing the importance of the decal and never be explained by health workers at the first checkups. While 7 (60%) of pregnant mother's husband has not determined the place of labor, labor companion, potential blood donors and did not accompany the mother when the checkups. This study aims to determine the relationship of husband support, knowledge of third trimester pregnant women at health centers with the implementation P4K-Kassi Kassi Makassar.This research uses analytic survey with cross sectional approach, the population in this study is the third trimester pregnant women, using the formula Lameshow obtained sample 85 subjects with a sampling technique is purposive sampling.Statistical analysis showed the Chi-square test obtained significant value p value 0,000 (p<0,05) husband's support with coefficient value (Phi= 0,493), knowledge of third trimester pregnant women p value of 0,001 (p <0,05) with coefficient value (Phi= 0,357). So it can be concluded that there is a relationship of husband support, knowledge of third trimester pregnant women with P4K implementation. Therefore, the husband is expected to support the implementation of the plan P4K safe delivery and is able to prevent pregnancy complications. And for health workers can improve IEC counseling and evaluation of the execution P4K, in particular blood donor candidates planning and sticking stickers P4K at home pregnant women.